(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2009)
The subject of disclosure, transparency and corporate governance taking globally significant attention recently, especially after the collapse of many large companies because the level of disclosure and transparency is an important measure of the effectiveness and reliability of the system of governance in the companies, the equity in the provision of correct information and clear and complete in a timely manner to all stakeholders in the life of the company with whom in relation strengthen the confidence the company’s management systems and automatic guide the staff and the decision-making. The research aims to shed light on the concept of corporate governance, and the reasons and motives of the spread of this concept in recent years in many countries of the world and the efforts of international, regional and local levels to identify with this concept and how it applied to the ground and know the level of disclosure and transparency to be achieved in light of corporate governance and the relevance of disclosure and transparency reports in accordance with international accounting standards and local rules. With the research and discuss the role of the comptroller in the disclosure and transparency, as one of the main foundations for the concept. To achieve the research’s aim , divided into four chapters, devoted its first chapter, the methodology, in the second quarter was devoted to the conceptual framework for corporate governance and its importance and its objectives, principles and financial reporting and corporate governance and its relation to disclosure and transparency and the role and responsibility of the comptroller and the procedures for confirmation of the relevance and adequacy of disclosure and healing in the Corporate Governance The third chapter was devoted to the analytical study of the role of the comptroller in the promotion of transparency and disclosure in the financial statements under the governance of a number of Iraqi companies, and reports of auditors on these companies, and analyze the results of the questionnaire form, and compared with the analytical study of the reports of auditors and financial statements of companies and evaluate the study sample the appropriateness and adequacy of disclosure Chapter IV specified to the conclusions and recommendations.